Analysis of the Promotion Mix Strategy on the Number of Martabe Savings Customers at PT Bank Sumut, Tembung Branch Office - Immanuel Edy Suranta Sebayang (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The subject of this research is "Analysis of Promotion Mix Strategies on the Number of Martabe Savings Customers PT Bank SUMUT Tembung Branch Office." To formulate the problem, this study seeks to determine the following: (a) the relative importance of advertising variables in determining the number of Mart-Abe Savings customers; (b) the relative attractiveness of personal sales in increasing Mart-Abe Savings customers; (c) the relative importance of the Promotion Mix Strategy in influencing the number of Mart-Abe Savings customers; and (d) the role of the Strategy's Promotion Mix in increasing Mart-Abe Savings customers. The goals of this research were to ascertain the relative importance of advertising variables in influencing Martabe Savings customer numbers, to ascertain the relative attractiveness of personal sales in boosting customer numbers, to ascertain the impact of the Promotion Mix Strategy on customer numbers, and to ascertain the function of the Promotion Mix Strategy in boosting customer numbers. We use SPSS 20 for data processing. Both primary and secondary data are used as sources of information. To preserve Martabe, surveys are sent to consumers as a means of data collection. According to the study's findings, a promotional mix strategy can only succeed by including the following elements: advertising, sales promotion, personal sales, publicity, and direct marketing. With these components, the strategy is likely to attract customers.